Cloud computing in health sector - Ujan, Imran Anwar; Shah, Asadullah (Islamic Society of Statistical Sciences, 2023)
Cloud computing is recognised as an extremely beneficial application for businesses due to benefits including long-term cost savings, simple access to data at any time, and economics. In fact, today's customers can choose from a plethora of free cloud storage services that make it simple to store and distribute data across an entire organisation. The private and governmental sectors are both interested in bettering cloud data storage. Some of these initiatives, however, are just getting off the ground, and there are still technological and human factors concerns that need to be solved before they can be fully implemented. Research pertaining to health is the focus of this analysis. The most significant factors in cloud computing adoption were discovered to be technological readiness, human readiness, organisational support, environment, and security and privacy. We anticipate that this research will aid in expanding our understanding of and preparedness for adopting cloud computing.